2021
DOI: 10.1021/acs.jmedchem.1c01508
|View full text |Cite
|
Sign up to set email alerts
|

Berberine Molecular Recognition of the Parallel MYC G-Quadruplex in Solution

Abstract: The medicinal natural product berberine is one of the most actively studied and pursued G-quadruplex (G4)-ligands. The major G-quadruplex formed in the promoter region of the MYC oncogene (MycG4) is an attractive drug target and a prominent example and model structure for parallel G-quadruplexes. G4-targeted berberine derivatives have been actively developed; however, the analogue design was based on a previous crystal structure in which berberine binds as a dimer to a parallel G-quadruplex. Herein, we show th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 45 publications
1
21
0
Order By: Relevance
“…Our ligand complex structures demonstrate the importance of the shape of the ligand and the two flanking sequences in determining the binding specificity of Myc121. 25,26,28,29 Base recruitment is likely to be the key step for ligand recognition. Intriguingly, our systematic analysis of the four available NMR structures with Myc121 revealed that the flanking base is recruited in a conserved residue-specific way (Figure 9B).…”
Section: G-quadruplexesmentioning
confidence: 99%
See 1 more Smart Citation
“…Our ligand complex structures demonstrate the importance of the shape of the ligand and the two flanking sequences in determining the binding specificity of Myc121. 25,26,28,29 Base recruitment is likely to be the key step for ligand recognition. Intriguingly, our systematic analysis of the four available NMR structures with Myc121 revealed that the flanking base is recruited in a conserved residue-specific way (Figure 9B).…”
Section: G-quadruplexesmentioning
confidence: 99%
“…Our laboratory has been fascinated by G-quadruplex structures and functions and started this exciting journey in 2002 to study the biologically relevant intramolecular G-quadruplexes formed in human telomeres and oncogene promoters. In 2005 and 2006, we described the potassium solution structures of the G-quadruplexes formed in the c-Myc oncogene promoter and in human telomeres. , Since then, we have described the potassium solution structures and functions of G-quadruplexes formed in several other oncogene promoters, such as BCL2, VEGF, and PDGFR-β. Toward G-quadruplex-targeted small molecules, we have characterized the recognition of biologically relevant human telomeric G-quadruplexes and promoter G-quadruplexes, particularly c-Myc. ,,, One of our primary approaches, high-field nuclear magnetic resonance (NMR) spectroscopy, represents a major method for the determination of high-resolution G-quadruplex structures under physiologically relevant solution conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Most of these compounds have a planar aromatic ring system that can stabilize G4s. Several plant secondary metabolites (PSMs) have been shown to share this feature and bind G4s: fisetin, sanguinarine, thymoquinone, quercetin, and berberine [ 15 , 16 , 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…The loop and groove regions exhibited the most essential difference among the different G4s. 65 Thus, improving the selective binding of 19a to the c-MYC G4 might be related to this binding mode. 57,66 Because the loop structure is the essential binding site for NM23-H2 and BLM, the significant increase in 19a in disrupting protein/G4 interactions might result from this binding site being blocked.…”
Section: Interactions Between 19a and C-myc G4mentioning
confidence: 99%